Home care: uma análise - Ozaki, Veridiana Tonzar Ristori [UNESP] (2014)
The present work aims to study the bioethical implications of home care, when considered a form of health care, to protect Human Rights. Currently, home care is considered a modern practical assistance, both by health plans in the private sector and by public health sector policies. Home care represents a trend worldwide and in Brazil, it states humanization in attendance, release of hospital beds, infection rates reduction and patient quality of life improvement as advantages for its implementation. However, we try to understand how home care presents several moral and ethical issues related to the actors involved: the patient, the caregiver, the family and the multidisciplinary team. The work resorts to Bioethics of Intervention and Bioethics of Protection, two Bioethics strands developed after Principlism was proved insufficient in a context of large of social inequalities, which is the case of Brazil. From this perspective, it is possible to give a voice to the excluded, oppressed and vulnerable. It is in this sense that bioethics must resort to human rights, as a way to protect the right to health of the neediest. Thus, it is sought to demonstrate that Home Care is a sector that has vulnerable subjects (patient, caregiver, family), to which the public protection policies should be directed